2017
DOI: 10.1525/collabra.76
|View full text |Cite
|
Sign up to set email alerts
|

Metaphoric Gestures Facilitate Perception of Intonation More than Length in Auditory Judgments of Non-Native Phonemic Contrasts

Abstract: It is well established that hand gestures affect comprehension and learning of semantic aspects of a foreign language (FL). However, much less is known about the role of hand gestures in lower-level language processes, such as perception of phonemes. To address this gap, we explored the role that metaphoric gestures play in perceiving FL speech sounds that varied on two dimensions: length and intonation. English speaking adults listened to Japanese length contrasts and sentence-final intonational distinctions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
(60 reference statements)
4
28
0
Order By: Relevance
“…Although the descriptives support the direction of our hypotheses, the multinomial logistic regression analysis reveals that the difference between the three gesture conditions is not significant for the outcome in which learning takes place, which is of most interest for this study. This is in line with those prior studies that did not find an effect of gestural training in the context of L2 (supra)segment acquisition [14,15,16]. The absence of a significant difference between gesture conditions might be explained in several ways.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although the descriptives support the direction of our hypotheses, the multinomial logistic regression analysis reveals that the difference between the three gesture conditions is not significant for the outcome in which learning takes place, which is of most interest for this study. This is in line with those prior studies that did not find an effect of gestural training in the context of L2 (supra)segment acquisition [14,15,16]. The absence of a significant difference between gesture conditions might be explained in several ways.…”
Section: Discussionsupporting
confidence: 92%
“…This might be surprising, considering the fact that a visual cue such as a written accent explicitly guides the learner as to which syllable is to be emphasised within the word. However, it does corroborate prior research which shows that the specific context in which L2 phonology acquisition does or does not occur matters when it comes to the facilitating role of gestures [12,15,28]. In addition, the use of cognates, while alleviating semantic processing load, does result in the use of less balanced item lists.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of the experiment showed that there was no noticeable benefit for participants when they learned vowel length by viewing videos showing length gestures as opposed to viewing videos that did not show such gestures. More recently, Kelly et al (2017) suggested that it may be possible to safely narrow down the effective use of perhaps the utility of visuospatial gestures in pronunciation learning is limited to the use of pitch gestures for the learning of intonation patterns (but not thus excluding the use of various types of metaphoric gestures for the study of duration). There might be a set of several possible reasons that can explain for the discrepancy between the results of the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to suggest that the type of metaphorical gestures used by Kelly, Hirata, and colleagues (Hirata & Kelly, 2010;Hirata et al, 2014;Kelly & Lee, 2012;Kelly et al, 2017) may have had an influence too. Specifically, the mora gestures used in the studies of Kelly, Hirata, and colleagues (e.g., the short vertical chopping movements) might have come across as "nonintuitive" to English speakers and thus did facilitate (or even hindered) their learning of durational information in the second language (see also the comments on the lack of effectiveness of length gestures in Kelly et al, 2017). The fact that other studies like Gluhareva and Prieto (2017) have found that observing other types of rhythmic gestures (e.g., beat gestures) has a positive effect on general pronunciation results leads us to suspect that perhaps the pitch gestures must seem natural to have positive results.…”
Section: Discussionmentioning
confidence: 99%